Admiral Gorshkov: the man who challenged the U.S. Navy - Polmar, Norman (Naval Institute Press, 2019)
"This is a book about a man and his ability to change a culture and to create a powerful navy that was radically different than traditional navies. And he accomplished this despite strong opposition from the nation's Army-dominated power structure. The Russian Navy that is at sea in the 21st Century is to a significant degree based on the fleet that this man built.This Russian Navy that sent a nuclear-propelled battlecruiser into the Caribbean in 2008 supported the Soviet combat actions in Syria beginning in 2015 and fired missiles from surface ships and a submarine into "rebel" areas in Syria can trace its "roots" directly to Admiral of the Fleet of the Soviet Union Sergei G. Gorshkov. "--